42.1 AUDITORY HALLUCINATIONS ACROSS THE PSYCHOSIS SPECTRUM: EVIDENCE OF CEREBELLAR DYSCONNECTIVITY. (9th April 2019) - Shinn, Ann; Hwang, Melissa; Roh, Youkyung; Talero, Jessica; Cohen, Bruce; Baker, Justin; Ongur, Dost
Abstract: Background: Auditory hallucinations (AH) are most commonly associated with schizophrenia (SZ), but they are non-specific, also occurring in up to 48% of bipolar disorder (BP) patients. It is well-established that SZ and BP, especially BP with psychotic features, are syndromes with significant genetic and clinical overlap. Despite how common auditory hallucinations are in BP, the neuroimaging literature on the topic is sparse. Many groups have studied abnormalities of resting state functional connectivity (FC) associated with AH in schizophrenia, but to our knowledge there are no published studies to date of FC associated with auditory hallucinations in BP. In this transdiagnostic investigation, we sought to identify functional connectivity (FC) abnormalities associated with AH across the spectrum of psychosis, including SZ and BP. Methods: Participants were 93 individuals with lifetime AH (69 SZ, 24 BP) and 63 without (NAH) (17 SZ, 46 BP), categorized using item B16 in the Structured Clinical Interview for DSM-IV-TR (SCID), which asks about lifetime auditory hallucinations. We acquired high-resolution structural scans and resting state blood oxygenation level dependent (BOLD) images (124 volumes, TR/TE 3000ms/30ms) on a 3T Siemens Tim Trio scanner at McLean Hospital. We used CONN v17e for resting state FC analysis. In addition to standard preprocessing, we used the ARtifact detection Tool (ART) to identify outlier time points, included only individuals with < 20 motion outliers, and performed rigorous denoising. For group-level analysis, we compared AH to NAH, adjusting for motion and other symptom dimensions. We performed ROI-to-ROI analysis, looking at BOLD time-course correlations across the 48 cortical and 21 subcortical regions of the Harvard-Oxford atlas and 26 cerebellar regions from the Automated Anatomical Labeling (AAL) atlas, using a significance threshold of p<0.05, FDR-corrected. As diagnosis, hallucinations in other (non-auditory) modalities, negative symptom severity, mania severity, and depression severity were statistically significantly different between AH and NAH, we controlled for these factors, in addition to motion, in our FC analysis. Results: We found that patients with auditory hallucinations had increased cerebello-cerebral cortical and cerebello-subcortical connectivity, compared to patients who have never had auditory hallucinations. In particular, we found hyperconnectivity between cerebellar subregions and frontal (left precentral gyrus, bilateral orbitofrontal cortices, and left inferior frontal gyrus), temporal (right middle temporal gyrus, bilateral planum temporale, right Heschl's gyrus, and bilateral fusiform cortices), parietal (left superior parietal lobule and bilateral parietal opercula), and subcortical regions (left nucleus accumbens and left thalamus). Conclusions: Our findings of aberrant cerebello-cerebral cortical and cerebello-subcortical connectivity are intriguing in light of growing evidence for the role of the cerebellum in integrating higher-level brain processes as well as for cerebellar abnormalities in both SZ and psychotic BP. Abnormal connectivity involving the cerebellum may play a more central role in the pathophysiology of AH than described in leading models of AH.